Locked‐in–like fulminant infantile Guillain–Barré syndrome associated with herpes simplex virus 1 infection. Issue 1 (1st October 2015) - Dilena, Robertino; Strazzer, Sandra; Esposito, Susanna; Paglialonga, Fabio; Tadini, Laura; Barbieri, Sergio; Giannini, Alberto
ABSTRACT: Introduction: Guillain–Barré syndrome (GBS) may rarely manifest as a peripheral locked‐in syndrome. Methods: Clinical and instrumental features of a fulminant form of infantile GBS were assessed. Results: After 2 days of rhinitis, a 6‐month‐old infant was intubated in the emergency room for sudden‐onset respiratory failure. Neurological examination showed generalized areflexic flaccid paralysis with no detectable interaction, which resembled a coma. Brain MRI was normal. Lumbar puncture showed pleocytosis (43 cells/mm 3 ) and herpes simplex virus 1 (HSV1) PCR positivity. EEG showed normal sleep–wake cycles, and EMG demonstrated nerve inexcitability. Acyclovir and immunoglobulins provided no benefit. After 1 week, lumbar puncture showed albuminocytological dissociation (protein 217 mg/dl). Plasmapheresis was then started, and progressive improvement occurred. At age 1 year, the child had recovered well with residual distal lower limb hyporeflexic weakness. Conclusions: A fulminant infantile GBS variant presenting as peripheral locked‐in syndrome can be associated with HSV1 infection likely due to autoimmune cross‐reactivity. Muscle Nerve 53 : 140–143, 2016